The Incorporation of High Order Thinking Skills in Exercises of the Eleventh Graders English Textbook - Jihan Fakhira; Ifan Iskandar (Lembaga Penelitian dan Pengabdian kepada Masyarakat dan Program Studi Pendidikan Bahasa Inggris Fakultas Bahasa dan Seni Universitas Negeri Jakarta, 2020)
This study was qualitative research using content analysis that aimed to investigate to what extent high order thinking skills (HOTS) are incorporated in the reading exercises of English textbook for 11th graders and to describe how HOTS are incorporated in the reading exercises. This study used Bloom’s Revised Taxonomy (BRT) table and the table of description was used to examine 107 essay reading exercises that come after every reading passage in a textbook published by the Ministry of Education and Culture of Indonesia. The findings showed that (1) the HOTS in the reading questions were available in 50 questions (46,7%) while the LOTS were in 57 questions (53,3%). (2) The HOTS questions required students to analyze the storyline from the reading passage, to argue their opinion or judge if they liked the reading text, to assess their own knowledge as their awareness were raised or changed toward the topic, and the last to create a new ending of the story. The findings of this research are expected to be the references for teachers to check the incorporation of HOTS in the exercises before they give to the students.